A Quantum Mechanism Study of the C-C Bond Cleavage to Predict the Bio-Catalytic Polyethylene Degradation - Xu, Junyu; Cui, Ziheng; Nie, Kaili; Cao, Hao; Jiang, Min; Xu, Haijun; Tan, Tianwei; Liu, Luo (Frontiers in Microbiology, 2019)
The growing amount of plastic waste ending up in landfills and in the oceans has become a global concern. Particularly, polyethylene (PE) and polystyrene (PS) are considered as notably recalcitrant to biodegradation due to the carbon-carbon backbone that is highly resistant to enzymatic degradation via oxidative reactions. The present research investigated the catalytic mechanism of P450 monooxygenases by quantum mechanics to determine the bio-catalytic degradation of PE or PS. The findings indicated that the oxygenase-induced free radical transition caused the carbon-carbon backbone cleavage of aliphatic compounds. This work provides a fundamental knowledge of the biodegradation process of PE or PS at the atomic level and facilitates predicting the pathway of plastics' biodegradation by microbial enzymes.